2016
DOI: 10.1534/g3.115.022087
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Universal Genotyping Array: From Substrains to Subspecies

Abstract: Genotyping microarrays are an important resource for genetic mapping, population genetics, and monitoring of the genetic integrity of laboratory stocks. We have developed the third generation of the Mouse Universal Genotyping Array (MUGA) series, GigaMUGA, a 143,259-probe Illumina Infinium II array for the house mouse (Mus musculus). The bulk of the content of GigaMUGA is optimized for genetic mapping in the Collaborative Cross and Diversity Outbred populations, and for substrain-level identification of labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
254
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 232 publications
(257 citation statements)
references
References 51 publications
3
254
0
Order By: Relevance
“…Because our sample contained 405 opposite-sex siblings, we were able to identify and resolve sample mix-ups by comparing genetic kinship 406 estimates to kinship estimated from the LG x SM pedigree (described in the Supplemental Methods). In 407 addition, we re-genotyped 24 mice on the GigaMUGA (Morgan et al 2015) to evaluate GBS variant calls 408 (Supplemental Table S5 lists concordance rates at various stages of our pipeline; see Supplemental 409…”
Section: ) (See Supplemental Methods and 398mentioning
confidence: 99%
See 1 more Smart Citation
“…Because our sample contained 405 opposite-sex siblings, we were able to identify and resolve sample mix-ups by comparing genetic kinship 406 estimates to kinship estimated from the LG x SM pedigree (described in the Supplemental Methods). In 407 addition, we re-genotyped 24 mice on the GigaMUGA (Morgan et al 2015) to evaluate GBS variant calls 408 (Supplemental Table S5 lists concordance rates at various stages of our pipeline; see Supplemental 409…”
Section: ) (See Supplemental Methods and 398mentioning
confidence: 99%
“…1A). Even before 284 imputation, GBS yielded nearly 50% more informative SNPs compared to the best available SNP 285 genotyping chip (Morgan et al 2015) at about half the cost (Supplemental Fig.S1). 286 .…”
Section: S1) 194mentioning
confidence: 99%
“…These samples were genotyped on one of the MUGA, MegaMUGA, or GigaMUGA (Neogen, Lincoln, NE) array platforms (Morgan et al 2016a). Genotype data from DO mice are being archived at http://do.jax.org, and will also be accessible from the Mouse Phenome Database (http://mpd.jax.org).…”
Section: Methodsmentioning
confidence: 99%
“…Novel alleles presented here have already been used to increase the utility of SNP arrays for genotyping of wild mice (Morgan et al 2016a). We provide tools to browse the variants, the underlying read alignments, and the raw reads (see Data Availability in Materials and Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…R2d2 was first identified in WSB/EiJ, a M. m. domesticus strain derived from mice trapped in Centreville, MD. SNP genotyping data (Yang et al 2011; Didion et al 2012; Morgan et al 2016a) indicated that ZALENDE/EiJ harbors the high-copy ( i.e. , distortion-associated) R2d2 allele, while LEWES/EiJ—derived from mice trapped only ∼100 km away from Centreville—has the low-copy ( i.e.…”
mentioning
confidence: 99%